Specific Features of Expressive Vocabulary (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In some scientific books expressiveness is the state of showing what someone thinks or feels. In vocabulary to express our thoughts we can use expressive vocabulary to deliver our ideas in a clear way. That’s why this article describes about some specific features of expressive vocabulary.